Influence of pyrolysis conditions on the mercury removal characteristics and physicochemical properties of biomass coke. (1st April 2022) - Zhao, Shilin; Luo, Hui; Ma, Anjun; Xie, Wen; Sun, Kang; Sun, Zhiqiang
Highlights: The pyrolysis temperature and atmosphere have great influence on Hg 0 removal of BC. N2  + 7% O2, higher pyrolysis temperature and heating rate develop the pore structure. BC-N2  + 7% O2 -800-10 has the best Hg 0 removal rate of 34.89% under all the pyrolysis conditions. Hg 0 removal of BC mainly by chemical adsorption with main content of HgO. Abstract: Effects of pyrolysis conditions, including pyrolysis temperatures, pyrolysis atmosphere, and heating rate, on Hg 0 removal of wood chip-based biomass coke (BC) under the basic simulated flue gas were systematically studied. The BET, SEM, FTIR, XPS and Hg-TPD were used to analyze the physicochemical properties and specific mercury compounds. The results show that the final pyrolysis temperature and pyrolysis atmosphere have greater influence on the mercury removal performance while heating rate affects little. The BC-N2  + 7%O2 -800-10 has the best Hg 0 removal efficiency under all the pyrolysis conditions, mainly due to the good pore structure and abundant surface oxygen-containing functional group. N2  + 7% O2, higher pyrolysis temperature and heating rate benefit for BC's pore structure development. Oxygen-containing functional groups of OH, CO and COO are the main functional groups on the BC surface, which promotes Hg 0 adsorption. The physically adsorbed Hg 0 and more chemically adsorbed HgO are the main mercury compounds in the used BC.